2017
DOI: 10.1007/s00338-017-1581-x
|View full text |Cite
|
Sign up to set email alerts
|

Trophic designation and live coral cover predict changes in reef-fish community structure along a shallow to mesophotic gradient in Hawaii

Abstract: Reef-fish community structure and habitat associations are well documented for shallow coral reefs (\20 m) but are largely unknown in deeper extensions of reefs (mesophotic reefs; [30 m). We documented the community structure of fishes and seafloor habitat composition through visual observations at depth intervals from 3 to 50 m in West Hawaii. Community structure changed gradually with depth, with more than 78% of fish species observed at mesophotic depths also found in shallow reef habitats. Depth explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
4
13
0
Order By: Relevance
“…This study combined diver and submersible surveys of the Bermuda slope and the flank of Plantagenet Bank to investigate fish assemblages covering a depth range from 15 to 305 m by incorporating both abundance and biomass data, the latter of which are rarely collected from underwater video surveys. As has been found in other studies from shallow and mesophotic reefs (e.g., Fukunaga et al, 2016;Lindfield et al, 2016;Kane and Tissot, 2017;Rocha et al, 2018), the fish assemblages of Bermuda and Plantagenet Bank showed strong depth-dependent structuring.…”
Section: Trends In Fish Abundance Biomass and Richness With Depthsupporting
confidence: 85%
See 1 more Smart Citation
“…This study combined diver and submersible surveys of the Bermuda slope and the flank of Plantagenet Bank to investigate fish assemblages covering a depth range from 15 to 305 m by incorporating both abundance and biomass data, the latter of which are rarely collected from underwater video surveys. As has been found in other studies from shallow and mesophotic reefs (e.g., Fukunaga et al, 2016;Lindfield et al, 2016;Kane and Tissot, 2017;Rocha et al, 2018), the fish assemblages of Bermuda and Plantagenet Bank showed strong depth-dependent structuring.…”
Section: Trends In Fish Abundance Biomass and Richness With Depthsupporting
confidence: 85%
“…Aided by advances in technical diving technology, recent biodiversity assessments of MCEs demonstrated that the upper MCEs (∼30-60 m) harbor biologically unique fish faunas with varying degrees of taxonomic overlap with shallower reef assemblages (Bejarano et al, 2014;Kane and Tissot, 2017;Semmler et al, 2017;Rocha et al, 2018). The magnitude of taxonomic overlap and the cut-off depth at which faunal breaks occur vary by location and are likely determined by a combination of local and regional, contemporary and historic environmental drivers and anthropogenic activities (Laverick et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite location differences, consistent patterns were observed between depths such as the decrease in species richness and the increase in biomass. This is a similar pattern exhibited in the transition between shallow and upper MCEs in many parts of the world (Abesamis et al, ; Andradi‐Brown et al, ; Bejarano et al, ; Kane & Tissot, ; Lindfield et al, ; Pinheiro et al, ). Also, it seems that despite the depth differences caused by benthic cover and inaccessibility to certain fishing methods, the dissimilarity caused by location has a stronger effect compared with depth.…”
Section: Discussionsupporting
confidence: 75%
“…However, a number of potential interactions between habitat characteristics and the associated fish community have been identified. For example, studies of fish assemblages from tropical Indo-Pacific and Atlantic shelf-breaks have reported the partitioning of trophic groups with depth [2,8,26,30,[32][33][34][35][36]. With increasing depth, the abundance of herbivores decreases and the abundance of planktivores increases [37].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of these benthic organisms is often highly depth-dependent. For instance, scleractinian corals are generally the most important component of shallower communities [2,34,36], while the representation of heterotrophic taxa such as sponges and gorgonians increase with depth as light decreases [26,39]. Similarly, other studies have suggested that physical attributes of the underlying benthos that increase habitat complexity, such as overall rugosity or the presence of key elements such as boulders or bedrock, often affects fish abundance [30], even in the absence of habitat-forming sessile invertebrates and algae.…”
Section: Introductionmentioning
confidence: 99%